IS ACHALASIA IN CHAGAS DISEASE DIFFERENT FROM IDIOPATHIC ACHALASIA? EXPERIENCE OF THE HOSPITAL DE CLÍNICAS DE PORTO ALEGRE - G. DA COSTA, DANIELA (2022)
Objetive: The objective of this study is to evaluate the differences between achalasia in Chagas’ disease and idiopathic achalasia in patients admitted to the Hospital de Clínicas de Porto Alegre, by analyzing epidemiologic, clinic, radiologic and manometric findings.Methods: Patients referred to the Hospital de Clinicas de Porto Alegre between November 1996 and December 2001 with suspicion of achalasia, later confirmed by esophageal manometry, were included in the study. In addition to manometric and radiologic findings, patients were assessed for age, sex, symptomsand symptomatic period.Results: Among 51 patients, nine (18%) presented positive serology for Chagas’ disease and 42 (82%) presented negative serology. The latter were considered carriers of idiopathic achalasia. The mean age of patients with achalasia in Chagas’ disease was 62 ± 15 years, while the mean age in the idiopathic group was 43 ± 18 years (P < 0.02). The symptomatic period for patients with achalasia in Chagas’ disease was 74 ± 47 months, and in the idiopathic group, 49 ± 35 months (P < 0.05). Dysphagia, regurgitation, thoracic pain and weight loss, values at the lower esophageal sphincter (basal pressure, post-deglutitive relaxation pressure/duration and total length) and at the esophageal body (amplitude and duration of the post-deglutitive waves) were similar in both groups.Conclusions: The only statistically significant differences found between the two groups were age and length of the symptomatic period, significantly greater in patients with achalasia in Chagas’ disease. These data suggest a greater resistance to the symptoms in older patients.